A numerical study of friction in isothermal EHD rolling-sliding sphere-plane contacts with spinning - Dormois, H. (2010)
This paper presents a study of the spinning influence on film thickness and friction in EHL circular contacts under isothermal and fully flooded conditions. Pressure and film thickness profiles are computed with an original full-system finite element approach. Friction was thereafter investigated with the help of a classical Ree–Eyring model to calculate the longitudinal and transverse shear stresses. An analysis of both the velocity and shear stress distributions at every point of the contact surfaces has allowed explaining the fall of the longitudinal friction coefficient due to the occurrence of opposite shear stresses over the contact area. Moreover in the transverse direction spinning favors large shear stresses of opposite signs, decreasing the fluid viscosity by non-Newtonian effects. These effects have direct and coupled consequences on the friction reduction that is observed in the presence of spinning. They are expected to further decrease friction in real situations due to shear heating.